Dairy Milk Is Associated with Increased Risk of Breast Cancer in the Adventist Health Study-2 (AHS-2) Cohort (P05-026-19). (13th June 2019) - Fraser, Gary; Miles, Fayth; Orlich, Michael; Jaceldo-Siegl, Karen; Mashchak, Andrew
Abstract: Objectives: Associations between diet and risk of breast cancer have been difficult to identify. Dairy milk has been hypothesized as a possible cause based on ecological data, also its sex hormone content (70% of dairy cows are pregnant), and likely ability to raise levels of insulin-like growth factor-1. We tested the dairy-breast cancer hypothesis in the Adventist Health Study-2 (AHS-2) cohort. Methods: AHS-2 is a national cohort that includes 61, 000 Adventist women, of whom 52, 795 formed an analytic cohort after exclusions. Many of these women did not consume dairy or consumed in minimal amounts, but more than half (i.e., the non-vegetarians) consumed dairy in usual amounts, on average. Soymilk was also consumed by many. Consumption of dairy, other foods and covariates was assessed from an extensive food frequency, health habits, and medical history questionnaire at study baseline (2002–7). During follow-up 1057 incident breast cancers were observed largely by matching with state cancer registries. Statistical analyses used proportional hazards regressions, adjusting for reproductive and other possible lifestyle risk factors. A calibration study with repeated 24-hour dietary recalls allowed for regression calibration. Results: Comparing 90th to 10th percentiles of intake, dairy milk was associated with a hazard ratio (HR) of 1.41 (95% CI: 1.15–1.72; P = 0.001), rising to 2.56 (95% CI:1.51–4.99; P < 0.001) with the less biased but less precise regression calibration procedure. Models substituting median intakes of soymilk for dairy milk (medians of users) predicted a HR of 0.66 (95% CI:0.51–0.85; P < 0.001). No associations were seen with cheese or yogurt. Associations were non-linear with steeper rises in breast cancer risk at intakes of dairy milk up to ¾ cup/day. No clear indication of protection was seen for soymilk after adjustment for dairy. Conclusions: In this population, dairy milk consumption is clearly associated with risk of breast cancer after adjusting for soy intake. This was not the case for cheese (known to have lower hormone content). More work is needed to define possible mechanisms. Those at higher risk of breast cancer may gain advantage by limiting milk intake and considering dairy substitutes. Funding Sources: National Institutes of Health, 1UO1CA152939]; World Cancer Research Fund (U.K.), grant 2009/93.